Revenge Reflected In John Greens Paper Town Novel (2008):A Behaviorist Perpsective - Tri Safitri, Emik; , Dr. Phil Dewi Candraningrum,M.Ed (2016)
The major problem of this study is revenge. Being hurt sometimes makes people angry. In this situation people will do anything to make them feel happy.The objective of this study is to analyze this novel based on the Behaviorist Perspective. The researcher employs qualitative method. The writer uses two data sources: primary and secondary. The primary data source of the study is Paper Towns novel by John Green. The secondary data of the study are taken from any information related to the novel. The technique of the Data Analysis is the descriptive qualitative research. Based on the analysis, the researcher gets some conclusions. The study shows that the problem faced by the major character. Revenge usually can be the best way for people, when they have purpose to take revenge, they will make plans to do their revenge. They do not care whether it is right or wrong.